David Rosenthal's Tirant lo Blanc turns 30. - REINHART, JAN (Scripta)
The groundbreaking English language translation of Tirant to Blanc by New York poet and academic David Rosenthal remains dominant three decades after its initial, and celebrated, release. Rosenthal's controversially fluid and concise rendering of the Valencian classic survived a serious challenge 20 years ago by a more literal version from a well-meaning amateur translator and journeyman academic backed by a leading U.S.-based Catalan scholar. The article reviews the controversy and compares the two versions, adding comments from some of the key critics.